Effect of Warm Red Ginger (Zingiber Officinale Var Rubrum) Compresses as Pain Reliever in Hypertensive Patients - Nurhanifah, Dewi; Khairunnisa, Khairunnisa; Rahayu, Sri (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2022)
The number of people with hypertension is increasing every year, and it is estimated that by 2025 there will be 1.15 billion people suffering from hypertension. The result of a preliminary study showed 2640 hypertensive patients in Pekauman Health Center. Interview results with five people who suffered from hypertension claimed that they experienced headaches up to the nape of the neck. Usually, they buy medicine at the nearest shop or use liniment such as balm to reduce the pain. This study aimed to determine the influence of warm red ginger (zingiber officinale var rubrum) compresses on reducing pain scale in hypertensive patients in the Pekauman Health Center area. The research was conducted using a pretest post-test design Quasi Experiment. The sample was 30 people with a purposive sampling technique. The treatment was given in the form of a warm red ginger compress for 15-20 minutes. Analysis using Wilcoxon test. There was a significant effect of giving red ginger (zingiber officinale var rubrum) warm compresses on reducing pain scale in hypertensive patients with a significant value of 0.000 (p<?0.05). Therefore, a warm red ginger compress could effectively reduce headaches in hypertension patients.